Chemical Physics - Bashir, M.; Dawood, Sara; Yagub, Musstafa; Sen, Tushar (Elsevier BV, 2015)
The study was conducted to evaluate the effectiveness of pine tree leaves as low cost adsorbent in the removal of anionic dye such as Congo red from its aqueous solution by adsorption. Batch adsorption experiments were carried out under different physio-chemical process parameters such as initial solution pH, dye concentration, temperature and adsorbent dose. It was observed that the adsorption process was pH dependentand the maximum pH occured at low pH. It was further observed that Freundlich maximum adsorption capacity (qm) was 25.8 mg/g at a pH of 3.1 and a temperature of 303 degrees Kelvin. Pseudo-first-order and pseudo-second-order models were used to examine the adsorption kinetic and mechanism of adsorption. It was found that the experimental data fitted well with pseudo-second-order kinetic model. Equilibrium data were best represented by Freundlich isotherm model among Langmuir and Freundlich adsorption isotherm models. Thermodynamic parameters such as delta G, delta H, and delta S were also calculated.